Technical assistance in the farming sector in Mexico: analysis of the 8th farming and forestry census - Cuevas Reyes, Venancio; Baca del Moral, Julio; Cervantes Escoto, Fernando; Aguilar Ávila José (Revista Mexicana de Ciencias Agrícolas, 2018)
The aim of this investigation was to determine, using the statistical information, obtained from the 8th Agriculture, Livestock and Forestry Census 2007, the importance of technical assistance of production units in Mexico to have elements that help in decision-making regarding this service. Databases were analyzed countrywide and by economic areas by obtaining relative frequencies. According to the Census, in Mexico, coverage of technical assistance is low, since only 3% of the del total farming units in the country have this service available, and only 11.7% find the lack of technical assistance and training to be a problem. Agriculture has 75.4% of the technical assistance, followed by livestock breeding with 19.3%, and forestry with 3.2%. Of this service, 70.8% is given by technicians, 17.7% by farmers, 2.8% by academic or research institutions, and finally, 1.5% by offices. In conclusion, environmental factors (loss in production to weather conditions) are the elements that most affect farming units; in fifth place, as a critical factor, are training and technical assistance. Policies must consider the problem from the point of view of the farmers in order to make resources for extension programs more efficient.